Comparative analysis of root canal irrigation in endodontic treatment of apical periodontitis in patients with root canal systems contaminated with Candida albicans - M. N. Medzhidov; T. A. Abakarov; G. N. Amirov; M. M. Medzhidov; M. G. Magomedova; R. M. Gareeva (Эндодонтия Today)
Apical periodontitis is an inflammatory process of the connective tissue complex forming the periodontal ligament (periodontum), localized around the apex of the tooth, caused by microbial invasion, located in the bacterial biofilm of the root canal system (RTS), with further progressive destruction of bone tissue, manifested on the X-ray lumens of different intensity.  The successful conservative treatment of the root canal depends on the availability of appropriate instruments, irrigation and root canal obturation. An important factor in the endodontic treatment of periodontitis is the removal of microbes, including fungi, from the complex three-dimensional root canal system. Various identification methods have revealed that fungi are more often found in secondary endodontic infections than in primary ones. Candida albicans (CA) plays an important role in endodontic treatment failure as the most significant fungus isolated from the root canal system. C. albicans is associated with root canal infections and is a potent pathogen for periapical tissue infection. Various virulence factors allow C. albicans to adhere to and penetrate the dentinal tubules. The yeast responds unfavorably to conservative root canal therapy because of the resistance of all oral Candida species to the commonly used topical medication, calcium hydroxide. Thus, the treatment of persistent cases of apical periodontitis requires alternative therapeutic methods and other drugs capable of elimination of this fungus species. Isolation with rhabberdam is important in preventing root canal contamination with saliva, in addition to prolonged contact with irrigation solutions.